2020
DOI: 10.1080/21691401.2020.1748885
|View full text |Cite
|
Sign up to set email alerts
|

ZnO/CNT@Fe 3 O 4 induces ROS-mediated apoptosis in chronic myeloid leukemia (CML) cells: an emerging prospective for nanoparticles in leukemia treatment

Abstract: Bashash (2020) ZnO/CNT@Fe 3 O 4 induces ROS-mediated apoptosis in chronic myeloid leukemia (CML) cells: an emerging prospective for nanoparticles in leukemia treatment, Artificial Cells,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Our recent study also reported that ZnO/RGO NCs show greater anticancer efficacy against cancer cells . The anticancer activity of ZnO-based NCs was found to be mediated through oxidative stress and apoptosis pathways. …”
Section: Introductionmentioning
confidence: 87%
“…Our recent study also reported that ZnO/RGO NCs show greater anticancer efficacy against cancer cells . The anticancer activity of ZnO-based NCs was found to be mediated through oxidative stress and apoptosis pathways. …”
Section: Introductionmentioning
confidence: 87%
“…Mesoporous silica nanoparticles (MSNs), featured with biochemical similarity with cell membranes, can both achieve anticancer and anti-angiogenesis purposes based on ROS [ 122 ]. Likewise, ZnO/CNT@FeO [ 123 ] and SASP/ZnO nanoparticles [ 124 ] can also increase ROS levels and facilitate cancer cell death. Though these studies are less reported about the detailed mechanisms, we hypothesis they must be closely related to the ROS-ncRNAs axis from above description.…”
Section: Therapeutic Implications Based On the Ros-ncrnas Axis In Cancermentioning
confidence: 99%
“…Based on unique properties such as minimal side effects and high specificity, magnetic iron oxide (Fe 3 O 4 ) NPs and ZnO NPs are assumed as the most attractive metal NPs and have attracted particular interest in scientific and medical communities [35,36]. Given the challenges with TKI treatment in CML patients [25], and based on significant antileukemic effects of a single agent of ZnO/CNT@Fe 3 O 4 nanocomposite against BCR/ABL-harboring CMLderived K562 cells [37], we investigated both the probable effect of this agent on Imatinib cytotoxicity and its underlying molecular mechanisms in CML cells. The results of the present study showed that simultaneous treatment with Imatinib and our synthesized ZnO/CNT@Fe 3 O 4 nanocomposite, which its successful formation was confirmed using TEM, Zeta potential measurement, DLS analysis, FTIR analysis, UV spectroscopy, and XRD, was indeed more effective in the reduction of both viability and metabolic activity in K562 cells as compared with Imatinib alone.…”
Section: Discussionmentioning
confidence: 99%